ANALYSIS OF THE INFLUENCE SOCIAL MEDIA USAGE INTENSITY ON DEPRESSION AMONG ADOLESCENTS AT HIGH SCHOOL IN SURABAYA - Fitri Masyithoh, Haibah; Rusyid, Ghozali (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to examine the influence of social media usage intensity on depression levels among adolescents. Adolescents are a vulnerable age group prone to various psychological issues, including depression, which can be influenced by social media use in the digital era. While social media offers numerous benefits, it can also contribute to social pressure and anxiety. Method: This research employed a quantitative approach using the Kolmogorov-Smirnov normality test and simple linear regression analysis. Results: The findings indicate a significant relationship between the intensity of social media use and adolescent depression levels, with an F-value of 4.281 and a p-value of 0.042 (p < 0.05). In other words, higher intensity of social media usage is associated with an increased likelihood of experiencing depressive symptoms. However, this effect is also influenced by usage patterns, social support, and individual psychological conditions. Novelty: These results highlight the importance of regulating adolescent social media use and the need for early intervention to mitigate its negative impact on mental health.